Crime prevention – the result of the effectiveness of criminal legal. (Journal of actual problems of jurisprudence, 2016)
The article discusses the prevention of juvenile delinquency. Also disclosed is a problem of efficiency to combat juvenile delinquency.
Keywords: crime prevention; Criminal legal; efficiency; effectiveness of the fight against crime